Management of Extra-Uterine Pregnancies at the Community Clinic - Songo-Kette Gbekere, Thibaut Boris Clavaire; Koirokpi, Alida; Kogboma Wongo, Rose de Lima; Serdouma, Candy Marie Paule; Imbatia, Severin Saturnin Heya; Ngbale, Norbert Richard; Sepou, Abdoulaye (European Scientific Journal, ESJ, 2024)
Ectopic pregnancy (EP) is an obstetric emergency affecting women in the first trimester of pregnancy. We decided to find out more about the management of these women. This was a cross-sectional study over a period of 6 months, from 1st November 2022 to 29th April 2023, covering patients operated on and medically treated for EP at the Community University Hospital(CHUC). During this period, we recorded 103 cases of ectopic pregnancy out of 1659 deliveries, representing a frequency of 6.2%. Patients under 35 years of age were the most common (88.3%). The majority of our patients had reached secondary school (54.4%) and were multiparous (33%). The gestational age of 8 - 12 SA was the most affected at the time of consultation. Radical surgery remains the most widely used treatment, accounting for 84.2% of cases in our study. Ectopic pregnancy is an extreme obstetric emergency in the first trimester which requires appropriate management. The best treatment is primary prevention by avoiding risk factors.